Proteomics and the Analysis of Proteomic Data: 2013 Overview of Current Protein‐Profiling Technologies. Issue 1 (1st March 2013) - Bruce, Can; Stone, Kathryn; Gulcicek, Erol; Williams, Kenneth
Abstract: Mass spectrometry has become a major tool in the study of proteomes. The analysis of proteolytic peptides and their fragment ions by this technique enables the identification and quantitation of the precursor proteins in a mixture. However, deducing chemical structures and then protein sequences from mass‐to‐charge ratios is a challenging computational task. Software tools incorporating powerful algorithms and statistical methods improved our ability to process the large quantities of proteomics data. Repositories of spectral data make both data analysis and experimental design more efficient. New approaches in quantitative and statistical proteomics make possible a greater coverage of the proteome, the identification of more post‐translational modifications, and a greater sensitivity in the quantitation of targeted proteins. Curr. Protoc. Bioinform . 41:13.21.1‐13.21.17. © 2013 by John Wiley & Sons, Inc.